Leaving Berlin - Kanon, Joseph 1946- (Simon & Schuster, 2014)
"From the bestselling author of Istanbul Passage...called a "fast-moving thinking man's thriller" by The Wall Street Journal...comes a sweeping, atmospheric novel of postwar East Berlin, a city caught between political idealism and the harsh realities of Soviet occupation. Berlin 1948. Almost four years after the war's end, the city is still in ruins, a physical wasteland and a political symbol about to rupture. In the West, a defiant, blockaded city is barely surviving on airlifted supplies; in the East, the heady early days of political reconstruction are being undermined by the murky compromises of the Cold War. Espionage, like the black market, is a fact of life. Even culture has become a battleground, with German intellectuals being lured back from exile to add credibility to the competing sectors. Alex Meier, a young Jewish writer, fled the Nazis for America before the war. But the politics of his youth have now put him in the crosshairs of the McCarthy witch-hunts. Faced with deportation and the loss of his family, he makes a desperate bargain with the fledgling CIA: he will earn his way back to America by acting as their agent in his native Berlin. But almost from the start things go fatally wrong. A kidnapping misfires, an East German agent is killed, and Alex finds himself a wanted man. Worse, he discovers his real assignment...to spy on the woman he left behind, the only woman he has ever loved. Changing sides in Berlin is as easy as crossing a sector border. But where do we draw the lines of our moral boundaries? Betrayal? Survival? Murder? Filled with intrigue, and the moral ambiguity of conflicted loyalties, Joseph Kanon's new novel is a compelling thriller and a love story that brings a shadowy period of history vividly to life"..